2020
DOI: 10.1177/0272989x20969683
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patient Preparedness and Confidence in Discussing Advance Directives for End-of-Life Care with Health Care Providers in the United States and Japan

Abstract: Background The low completion rate of advance directives (ADs) has received attention in Japan and the United States, as policy makers and health care professionals face aging populations with multiple comorbidities. Among the barriers to AD planning, cultural values and attitudes appear to be particularly influential. A comparison of culturally distinct societies provides a deeper understanding of these barriers. Through such an approach, this study identifies strategies for increasing AD planning among late-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 110 publications
(119 reference statements)
0
8
0
Order By: Relevance
“…However, in the context of Japan, where the surplus of psychiatric and chronic care beds seems to be a key driver for prolonging hospitalisation and increasing IMEP75, spending on outpatient care may contribute little to reducing IMEP75. Furthermore, while more primary care visits in the preceding year is linked to reduced end-of-life hospital utilisation and costs in the US (44), the low adoption of advance directives in Japan may be associated with avoidable emergency transfers and hospital admissions (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the context of Japan, where the surplus of psychiatric and chronic care beds seems to be a key driver for prolonging hospitalisation and increasing IMEP75, spending on outpatient care may contribute little to reducing IMEP75. Furthermore, while more primary care visits in the preceding year is linked to reduced end-of-life hospital utilisation and costs in the US (44), the low adoption of advance directives in Japan may be associated with avoidable emergency transfers and hospital admissions (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Health-care research also suggests that interdependent and independent self-construal may be made salient by the decision aid experience (Alden et al, 2014;Friend and Alden, 2021).…”
Section: Conceptual Model and Study Hypothesesmentioning
confidence: 99%
“…As part of the scenario, respondents were presented with the possible harms and benefits of each treatment option followed by patient narratives and a value clarification exercise. Scenario design followed similar vignette-based research on treatment decision-making (Friend and Alden, 2021). Due to their ability to increase both internal and external validity in experimental designs, vignettes are widely used in health-care research (Evans et al, 2015;Sheringham et al, 2021).…”
Section: Participants and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Dunn et al [6] found that only 26% of patients older than 65 years undergoing surgery for hip fractures had advanced care planning documents uploaded into their EMR. Although factors associated with engaging in endof-life care planning such as higher income, higher levels of education, and having strong interpersonal relationships have been established [9,13,14,25,26,29], to the best of our knowledge, the association of patient demographics and economic well-being on the presence of advanced care planning documents in the EMR for patients older than 65 years undergoing repair of a hip fracture has not been explored. Additionally, the research by Dunn et al [6] was a single-institution study, so further study is warranted to explore the generalizability of their results.…”
mentioning
confidence: 99%